The Influence of Health Education Using Booklet Media on Mother's Knowledge in Providing MPASI - Hairunnissa, Hairunnissa; Aprillia, Novitasari (Asy-Syifa : Journal of Science and Technology Nursing, 2025)
Purpose:The purpose of this study is to determine the effect of health education using booklet media on mothers’ knowledge regarding appropriate complementary feeding (MPASI) for infants aged 6–24 months as an effort to prevent malnutrition and stunting. Methods:This study employed a descriptive design with a case study approach. The subjects consisted of 30 mothers of toddlers at Posyandu Melati, Jl. Pasar Baru Barat Karet II RW 005, Kelurahan Karet Tengsin, Kecamatan Tanah Abang, Central Jakarta. The sample size was determined using the Slovin formula. Health education was delivered through booklet media focusing on the timing, methods, and variations of MPASI. Data were collected by measuring mothers’ knowledge before and after the educational intervention. Results:The results showed a significant improvement in mothers’ knowledge after health education. Prior to the intervention, 18 respondents (60%) were in the poor knowledge category, 9 respondents (30%) had adequate knowledge, and 3 respondents (10%) had good knowledge. After the intervention, the poor knowledge category decreased to 0 respondents (0%), the adequate category decreased to 6 respondents (20%), while the good knowledge category increased to 24 respondents (80%). Conclusions: Health education on complementary feeding using booklet media is effective in increasing mothers’ knowledge regarding MPASI. Therefore, support from health workers is essential to continuously provide structured and cooperative health education, particularly for mothers who are beginning to introduce MPASI to their toddlers.